As construções relativas na Fala de Vitória/ES: uma perspectiva sociolinguística - Santos, André Poltronieri (2020)
We study, in this thesis, the variation of the relativization strategies on spoken portuguese in Vitória/ES. We have analyzed a sample of speech consisting of forty six interviews from the Project Spoken Portuguese in the City of Vitória (PortVix). The speakers were stratified in four age groups, three levels of schooling and gender (YACOVENCO et al., 2012). We have observed that the behavior of the relativization strategies varies according to the syntactic function of the relative pronoun. Thus, the syntactic functions were rearranged in three groups, according to the possibilities of variation. The data were submitted to statistical analysis with the program package GoldVarb X (SANKOFF; TAGLIAMONTE; SMITH, 2005). The selected groups of factors were different for each of the three groups. The results, in general, converge with the ones found in other researches about the variation of relative clauses in the speech of other cities. The variables that favor more strongly the copy retention variant were, especially, the [+ human] trace of the noun phrase head and environments with greater distance , which is related to the concept Mollica (1977; 1997) has named syntactic processing. As for the relative pronouns, the results show that que is, as we have already expected, the most frequent. The high frequency of subject and direct object relative clauses without the pronoun retention, as Silva e Lopes (2007) attest, has been weakening semantically the relative pronoun que and, consequently, generalizing the usage of this pronoun on prepositional variants, i.e., on prepositional phrase choppping, whose structure is similar to standard subject and direct object relative clauses.